Bumble bees and honey bee abundances collected in agricultural landscapes with and without flower strips and honey bee hives - Bommarco, Riccardo (Swedish University of Agricultural Sciences, 2021)
Wild bee declines in agricultural landscapes have led farmers to supplement crops with honey bees. Simultaneously, environmental subsidy and conservation programmes have incentivized farmers to establish flower strips to support wild and managed pollinators. To find out if flower strips enhance, and competition from honey bees suppresses, wild bees in the landscape and across seasons, we surveyed bumble bee and honey bee abundances in 16 sites in Sweden in summer 2018 and spring 2019. The centre of each site (2 km radius) was with or without an annual flower strip, and with or without added honey bee hives. We surveyed bees in each flower strip and in linear habitats in the landscape around each site, such as field edges and road verges. In the following spring, we surveyed bumble bee queen abundance in each site. We show that adding flower strips benefits bumble bee queen abundance the following year, but this effect is diminished if honeybee hives are added. In sites with flower strips, added honey bee hives reduced male bumble bee abundance. Our relatively small flower strip areas bolstered bumble bee population growth across seasons, probably by relieving a resource bottleneck. Adding honey bee hives in combination with flower strips to landscapes with few floral resources should be avoided as it cancelled the positive effect of flower strips.

Vilda bin har minskat i antal och jordbrukare har därför börjat använda även honungsbin tillsammans med blomremsor. För att ta reda på om blomremsor förstärker vilda bin och dämpar konkurrensen från honungsbin har förekomsten av humlor och honungsbin undersökts på 16 platser i Sverige under sommaren 2018 och våren 2019.

Se den engelska sidan för utförligare beskrivning.
Abundans av humlor och honungsbin i jordbrukslandskap med eller utan blomremsor och honungsbisamhällen
Keywords: Habitats and biotopes; Naturtyper och biotoper; Land use; Markanvändning; Species distribution; Arters utbredning; Apis mellifera; Honungsbi; Agroecology; Agroekologi; Bumble bee; Humla; Natural Sciences; Naturvetenskap; Ecology; Ekologi; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Farming; Areella näringar; Environment; Miljö